A TRIADIC EVALUATION OF NUMERICAL SYMBOLISM IN QUR'ANIC NATAWAFFAYANNAKA VERSES AND PROPHETIC BIOGRAPHY - Moh. Nadhif Nadhif; Bakri Muhammad Bakhiet; Ahmad Naweed Rahimi khamosh; Muhammad Yusron Shidqi (STKQ Al-Hikam Depok, 2026)
This article examines numerical symbolism in three Qur'anic verses that contain the phrase natawaffayannaka, namely QS. Yunus 10:46, QS. ar-Ra‘d 13:40, and QS. Ghafir 40:77. The study responds to a methodological problem in numerical i‘jaz research. Some studies treat numerical patterns as direct proof of divine design, while others reject them as arbitrary coincidence. Both positions often ignore the need for a transparent evaluative frame. This study uses a qualitative textual design supported by numerical-conceptual evaluation. It combines close reading, bounded numerical mapping, illustrative probability baselines, and cognitive-epistemological critique. The findings show that the surah sequence 10, 13, and 40 can be read as a cautious symbolic alignment with three common markers in the Prophet Muhammad's biography: the ten-year Medinan period, the thirteen-year Meccan mission, and the age of forty at the beginning of revelation. Yet statistical rarity does not prove intentionality. The pattern gains scholarly value only when it passes three checks: textual coherence, numerical transparency, and cognitive caution against post hoc pattern recognition. The article therefore proposes a triadic evaluation model for studying numerical symbolism in Qur'anic texts